2015
DOI: 10.1152/jn.00648.2015
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary reaction time and long-latency reflex modulation

Abstract: Forgaard CJ, Franks IM, Maslovat D, Chin L, Chua R. Voluntary reaction time and long-latency reflex modulation. J Neurophysiol 114: 3386 -3399, 2015. First published November 4, 2015 doi:10.1152/jn.00648.2015.-Stretching a muscle of the upper limb elicits short (M1) and long-latency (M2) reflexes. When the participant is instructed to actively compensate for a perturbation, M1 is usually unaffected and M2 increases in size and is followed by the voluntary response. It remains unclear if the observed increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 46 publications
3
27
0
Order By: Relevance
“…Furthermore, all these studies explored motor responses in the same passively displaced limb during the time window of LLR [34, 56, 57, 61]. Hence it was difficult to ascertain the suspected startling nature of kinematic stimuli, and, if startle signs were present in OOc or SCM, the superimposition of reflexive or voluntary responses in the limb being moved made a clear characterization of startle responses in the same extremity muscles difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, all these studies explored motor responses in the same passively displaced limb during the time window of LLR [34, 56, 57, 61]. Hence it was difficult to ascertain the suspected startling nature of kinematic stimuli, and, if startle signs were present in OOc or SCM, the superimposition of reflexive or voluntary responses in the limb being moved made a clear characterization of startle responses in the same extremity muscles difficult.…”
Section: Discussionmentioning
confidence: 99%
“…One g oal of our experimental design was to minimize or eliminate the engagement of voluntary responses to mechanical perturbation in the learning process so that we could attribute any observed learning directly to the neural mechanisms that generate feedback responses rather than learning from whatever mechanisms generate voluntary motor commands. We did this by using very short duration perturbations (20 ms) and instructing participants to not intervene with the perturbations, both of which have been previously shown elicit long-latency stretch reflexes (50-100 ms post-pert urbation) while reducing or eliminating associated voluntary responses (>100 ms post-perturbation) (Asatryan and Feldman, 1965;Crago et al, 1976;Ghez and Shinoda, 1978;Lee and Tatton, 1982;Calancie and Bawa, 1985;Lewis et al, 2005;Pruszynski et al, 2008;Schuurmans et al, 2009;Shemmell et al, 2009;Kurtzer et al, 2010;Forgaard et al, 2015Forgaard et al, , 2016Forgaard et al, , 2019Kurtzer, 2019) . Our paradigm did create the expected response profiles such as no reliable decrease in muscle activity after 100 ms post-perturbation with shoulder fixation, presumably because the evoked response in the voluntary epoch was minimal to begin with (Figure 4 A-B).…”
Section: Limitationsmentioning
confidence: 99%
“…First, we used mechanical perturbations with very short durations (20 ms) previously shown to elicit reflex responses but very weak or non-existent voluntary muscle responses (Ghez and Shinoda, 1978;Lee and Tatton, 1982;Lewis et al, 2005;Schuurmans et al, 2009;Kurtzer et al, 2010;Kurtzer, 2019) . Second, we instructed participants to not intervene with the mechanical perturbations previously shown to substantially reduce or eliminate voluntary muscle responses (Asatryan and Feldman, 1965;Crago et al, 1976;Calancie and Bawa, 1985;Shemmell et al, 2009;Forgaard et al, 2015Forgaard et al, , 2016Forgaard et al, , 2019 .…”
Section: Introductionmentioning
confidence: 99%
“…In a manner similar to previous studies Ravichandran et al, 2013;Forgaard et al, 2016) (Ravichandran et al, 2013;Forgaard et al, 2015). Integrated values for each epoch were taken from the rectified EMG traces on a trial-by-trial basis.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…Among many notable examples, the magnitude of the LLR scales based on target location , is sensitive to limb mechanics , and as traditionally investigated, the instruction of how to respond to a perturbation (Hammond, 1956) The issue of whether volitional characteristics of the LLR are produced through feedback gain changes in presumably supraspinal circuitry (Lee and Tatton, 1975;Pruszynski et al, 2014), or the appearance of a flexible feedback response only arises because a voluntary response is triggered early by the perturbation and superimposes onto the LLR (Rothwell et al, 1980;Manning et al, 2012) has been investigated for many years. Recent studies have consistently shown that LLR modulation begins at a shorter latency than the earliest possible voluntary response Forgaard et al, 2015). Despite this, many groups have shown that the magnitude of the LLR remains strongly related to volitional activity (Rothwell et al, 1980;Pruszynski et al, 2008;Manning et al, 2012;Crevecoeur et al, 2013).…”
Section: Introductionmentioning
confidence: 99%